Identification and functional characterization of GAA mutations in Colombian patients affected by pompe disease (2013)
Pompe disease (PD) is a recessive metabolic disorder characterized by acid ?-glucosidase (GAA) deficiency, which results in lysosomal accumulation of glycogen in all tissues, especially in skeletal muscles. PD clinical course is mainly determined by the nature of the GAA mutations. Although ~400 distinct GAA sequence variations have been described, the genotype-phenotype correlation is not always evident. In this study, we describe the first clinical and genetic analysis of Colombian PD patients performed in 11 affected individuals. GAA open reading frame sequencing revealed eight distinct mutations related to PD etiology including two novel missense mutations, c.1106 T > C (p.Leu369Pro) and c.2236 T > C (p.Trp746Arg). In vitro functional studies showed that the structural changes conferred by both mutations did not inhibit the synthesis of the 110 kD GAA precursor form but affected the processing and intracellular transport of GAA. In addition, analysis of previously described variants located at this position (p.Trp746Gly, p.Trp746Cys, p.Trp746Ser, p.Trp746X) revealed new insights in the molecular basis of PD. Notably, we found that p.Trp746Cys mutation, which was previously described as a polymorphism as well as a causal mutation, displayed a mild deleterious effect. Interestingly and by chance, our study argues in favor of a remarkable Afro-American and European ancestry of the Colombian population. Taken together, our report provides valuable information on the PD genotype–phenotype correlation, which is expected to facilitate and improve genetic counseling of affected individuals and their families. © SSIEM and Springer-Verlag Berlin Heidelberg 2012.